Rural Hospital Nursing Skill Mix and Work Environment Associated With Frequency of Adverse Events - Jessica G. Smith PhD, RN; Colin M. Plover PhD, RN; Moira C. McChesney; Eileen T. Lake PhD, RN, FAAN (SAGE Publishing, 2019)
Introduction: Although rural hospitals serve about one fifth of the United States, few studies have investigated relationships among nursing resources and rural hospital adverse events. Objectives: The purpose was to determine relationships among nursing skill mix (proportion of registered nurses [RNs] to all nursing staff), the work environment, and adverse events (medication errors, patient falls with injury, pressure ulcers, and urinary tract infections) in rural hospitals. Methods: Using a cross-sectional design, nurse survey data from a large study examining nurse organizational factors, patient safety, and quality from four U.S. states were linked to the 2006 American Hospital Association data. The work environment was measured using the Practice Environment Scale of the Nursing Work Index (PES-NWI). Nurses reported adverse event frequency. Data analyses were descriptive and inferential. Results: On average, 72% of nursing staff were RNs (range = 45%-100%). Adverse event frequency ranged from 0% to 67%, across 76 hospitals. In regression models, a 10-point increase in the proportion of RNs among all nursing staff and a one standard deviation increase in the PES-NWI score were significantly associated with decreased odds of frequent adverse events. Conclusion Rural hospitals that increase the nursing skill mix and improve the work environment may achieve reduced adverse event frequency.